Anode, electrochemical device and electronic device including said anode

JP7651711B2Active Publication Date: 2025-03-26NINGDE AMPEREX TECHNOLOGY LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023545333
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-29
Filing Date
2022-02-09
Publication Date
2025-03-26
Estimated Expiration
2042-02-09

Smart Images

  • Figure 0007651711000004
    Figure 0007651711000004
  • Figure 0007651711000001
    Figure 0007651711000001
  • Figure 0007651711000002
    Figure 0007651711000002
Patent Text Reader

Abstract

The present application relates to a negative electrode, an electrochemical device including the negative electrode, and an electronic device. The negative electrode includes a current collector and a negative electrode active material layer disposed on the current collector, the negative electrode active material layer includes negative electrode active material particles, the negative electrode active material particles include secondary particles, and the negative electrode active material layer includes a hole A, and the hole A has a diameter of 59 nm-73 nm as measured by mercury intrusion porosimetry, and the C004 / C110 value of the negative electrode active material layer is 6-20. An electrochemical device using the negative electrode provided in the present application has high capacity and improved cycle expansion resistance characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of energy storage, in particular to anodes, electrochemical and electronic devices including such anodes, and in particular to lithium ion batteries. [Background technology]

[0002] Electrochemical devices (e.g., lithium-ion batteries) are widely used due to their advantages of being environmentally friendly, having high operating voltage, large specific capacity, and long cycle life, and are currently the new green chemistry power source with the greatest potential for development in the world. Small lithium-ion batteries are generally used as power sources for portable electronic communication devices (e.g., portable video cameras, mobile phones, laptops, etc.), especially for high-performance portable devices. In recent years, medium- and large-sized lithium-ion batteries with high output characteristics have been developed and applied to electric vehicles (EVs) and large-scale energy storage systems (ESSs). As lithium-ion batteries are widely applied, their cycle performance has become an important technical issue to be resolved. Improving the active material in the electrodes is one of the research directions to resolve the above issues. Summary of the Invention [Problem to be solved by the invention]

[0003] In the prior art, graphite is mainly coated and carbonized. The surface coating layer suppresses the expansion between particles, while the coating reduces the polarization generation and the accumulation of side reaction products, thereby improving the problem of cycle expansion. However, this method seriously affects the energy density of the lithium ion battery, making it difficult to balance the overall performance of the lithium ion battery. In view of the above, there is a need to provide an improved active material, and anodes, electrochemical devices, and electronic devices manufactured using the same. [Means for solving the problem]

[0004] SUMMARY OF THE DISCLOSURE The present embodiments seek to solve, at least in part, at least one problem in the related art by providing a negative electrode, and electrochemical and electronic devices that include the negative electrode.

[0005] In one embodiment, the present application provides a negative electrode, comprising: a current collector; and a negative electrode active material layer disposed on the current collector, the negative electrode active material layer comprising negative electrode active material particles, the negative electrode active material particles comprising secondary particles, the negative electrode active material layer comprising pores A, the pores A having a diameter of 59 nm-73 nm as measured by mercury intrusion porosimetry, and a C004 / C110 value of the negative electrode active material layer being 6-20.

[0006] In some embodiments, the differential of the mercury intrusion rate of the hole A is 0.150-0.190 mL / g μm as measured by mercury intrusion porosimetry. -1 It is.

[0007] In some embodiments, the negative electrode active material layer includes pores B, and the pores B have a pore size of 661.6 nm-793.3 nm when measured by mercury intrusion porosimetry, and the differential of the amount of mercury intrusion in the pores B is 0.160-0.230 mL / g μm -1 It is.

[0008] In some embodiments, the volume ratio of pores B to pores A is 0.7:1-1.42:1.

[0009] In some embodiments, the negative electrode active material particles include At least one of the following is satisfied: (a) Dv50 of the negative electrode active material particles is 7.2-21.6 μm; (b) Dv90 of the negative electrode active material particles is 28.4-40 μm; (c) Dv10 of the negative electrode active material particles is 1.4-9.4 μm; and (d) Dv90 and Dn10 of the negative electrode active material particles satisfy Dv90 / Dn10≦26.

[0010] In some embodiments, the negative electrode active material particles have a powder particle size D1v50 before being pressed and a powder particle size D2v50 after being pressed at a pressure of 1t, and (D1v50-D2v50) / D1v50x100%≦25%.

[0011] In some embodiments, the specific surface area of ​​the negative electrode active material particles is 0.8-2.0 m 2 / g.

[0012] In some embodiments, the negative electrode active material particles have a specific surface area of ​​B1 before being pressed and a specific surface area of ​​B2 after being pressed at a pressure of 1 t, and (B2-B1) / B1×100%≦140%.

[0013] In another embodiment, the present application provides an electrochemical device comprising a negative electrode according to any of the embodiments of the present application.

[0014] In some embodiments, when the electrochemical device is discharged to a voltage of 3 V, the specific surface area of ​​the negative electrode active material particles is 1.9-2.4 m 2 / g.

[0015] In some embodiments, when the electrochemical device is charged to a voltage of 4.45 V, the maximum exothermic peak of the negative electrode active material layer is 280-330° C. as measured by DSC.

[0016] In some embodiments, when the electrochemical device is discharged to a voltage of 3 V, the powder particle size of the negative electrode active material particles is D a V50, and the powder particle diameter of the negative electrode active material after being pressed at a pressure of 1 ton is D b v50, (D a v50-D b v50) / D a v50×100%≦2%.

[0017] In some embodiments, when the electrochemical device is discharged to a voltage of 3 V, the negative electrode active material particles have a specific surface area of ​​B 11 And the specific surface area after being pressed with a pressure of 1t is B 22 (B 22 -B 11 ) / B 11 ×100%≦40%.

[0018] In another embodiment, the present application provides an electronic device comprising an electrochemical device according to any of the embodiments of the present application.

[0019] The present application improves the capacity and cycle expansion resistance characteristics of lithium ion batteries by optimizing the structure of the particles themselves and the degree of compounding between the particles.

[0020] Additional aspects and advantages of the present application are set forth in part in the following description, and are illustrated or explained by examples of the present application. [Brief description of the drawings]

[0021] In the following, in order to describe the embodiments of the present application, the drawings necessary for describing the embodiments of the present application or the prior art will be briefly described. It is clear that the drawings described below are only a part of the embodiments of the present application. Those skilled in the art can obtain drawings of other embodiments from the structures illustrated in these drawings without creative labor.

[0022] [Figure 1] FIG. 1 shows differential mercury penetration curves of the negative electrode active materials of Example 11 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present application will be described in detail below with reference to examples, which should not be construed as limiting the present application.

[0024] In the present application, Dv50 is the particle size, in μm, corresponding to the cumulative volume percentage of the negative electrode active material reaching 50%, Dv90 is the particle size, in μm, corresponding to the cumulative volume percentage of the negative electrode active material reaching 90%, and Dv10 is the particle size, in μm, corresponding to the cumulative volume percentage of the negative electrode active material reaching 10%.

[0025] It should be noted that quantities, ratios, and other numerical values ​​may be presented in a range format in this specification. Such range formats are for convenience and brevity and should be understood flexibly to include not only the numerical values ​​explicitly set forth as limiting the range, but also all individual numerical values ​​or subranges contained within said ranges as if each numerical value and subrange were expressly set forth.

[0026] In specific embodiments and in the claims, a list of items connected by the terms "one of," "one of," "a kind of," or other similar terms means any of the listed items. For example, if items A and B are listed, "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, "one of A, B, and C" means only A, only B, or only C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0027] In specific embodiments and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms means any combination of the listed items. For example, if items A and B are listed, "at least one of A and B" means A only, B only, or A and B. In another example, if items A, B, and C are listed, "at least one of A, B, and C" means A only, B only, C only, A and B (excluding C), A and C (excluding B), B and C (excluding A), or A, B, and C as a whole. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0028] Electrochemical Devices In one embodiment, the present application provides an electrochemical device including a positive electrode, a negative electrode, a separator, and an electrolyte.

[0029] In some embodiments, the electrochemical device of the present application includes, but is not limited to, a primary battery or a secondary battery.

[0030] In some embodiments, the electrochemical device is a lithium secondary battery.

[0031] In some embodiments, the lithium secondary battery includes, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0032] 1. Negative electrode The present embodiment provides a negative electrode, comprising: a current collector and a negative active material layer disposed on the current collector, the negative active material layer comprising negative active material particles, the negative active material particles comprising secondary particles, the negative active material layer comprising pores A, the pores A having a diameter of 59nm-73nm as measured by mercury intrusion porosimetry, and the C004 / C110 value of the negative active material layer being 6-20.

[0033] In some embodiments, the pore size of A is 59 nm, 60 nm, 61 nm, 62 nm, 63 nm, 64 nm, 65 nm, 66 nm, 67 nm, 68 nm, 69 nm, 70 nm, 71 nm, 73 nm, or a range consisting of any two of these values.

[0034] In some embodiments, the C004 / C110 value of the negative electrode active material layer is 6, 8, 10, 12, 14, 16, 18, 20, or a range consisting of any two of these values.

[0035] In some embodiments, the differential of the mercury intrusion rate of the hole A is 0.150-0.190 mL / g μm as measured by mercury intrusion porosimetry. -1 It is.

[0036] In some embodiments, the differential of the mercury intrusion amount of the hole A is 0.150 mL / g μm -1 , 0.160mL / g μm -1 , 0.170mL / g μm -1 , 0.180mL / g μm -1 , 0.190mL / g μm -1 or a range consisting of any two of these values.

[0037] In some embodiments, the negative electrode active material layer includes pores B, and the pores B have a pore size of 660 nm-800 nm when measured by mercury intrusion porosimetry, and the differential of the amount of mercury intrusion in the pores B is 0.160-0.230 mL / g μm -1 It is.

[0038] In some embodiments, the pore size of B is 660 nm, 670 nm, 680 nm, 690 nm, 700 nm, 710 nm, 720 nm, 730 nm, 740 nm, 750 nm, 760 nm, 770 nm, 780 nm, 790 nm, 790 nm, 800 nm, or a range consisting of any two of these values.

[0039] In some embodiments, the volume ratio of the holes B to the holes A is 0.7:1-1.42:1. In some embodiments, the volume ratio of the holes B to the holes A is 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.42:1, or a range consisting of any two of these values. When the volume ratio of the holes B to the holes A is within the above range, the area of ​​the negative electrode active material exposed to the electrolyte can be controlled, side reactions can be reduced, and the flow and infiltration of the electrolyte can be ensured and an increase in resistance can be avoided.

[0040] In some embodiments, the negative electrode active material particles satisfy at least one of: (a) a Dv50 of the negative electrode active material particles is 7.2-21.6 μm; (b) a Dv90 of the negative electrode active material particles is 28.4-40.0 μm; (c) a Dv10 of the negative electrode active material particles is 1.4-9.4 μm; or (d) a Dv90 and Dn10 of the negative electrode active material particles satisfy Dv90 / Dn10≦26.

[0041] In some embodiments, the Dv50 of the negative electrode active material particles is 7.2 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 21.6 μm, or a range consisting of any two of these values.

[0042] In some embodiments, the Dv90 of the negative electrode active material particles is 28.4 μm, 30 μm, 32 μm, 34 μm, 35.7 μm, 38 μm, 40 μm, or a range consisting of any two of these values.

[0043] In some embodiments, the Dv10 of the negative electrode active material particles is 1.4 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.4 μm, or a range consisting of any two of these values.

[0044] In some embodiments, Dv90 / Dn10 is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, or a range consisting of any two of these values.

[0045] In some embodiments, the negative electrode active material particles have a powder particle size D1v50 before being pressed and a powder particle size D2v50 after being pressed at a pressure of 1t, and (D1v50-D2v50) / D1v50x100%≦25%.

[0046] In some embodiments, the value of (D1v50-D2v50) / D1v50×100% is 1%, 3%, 6%, 9%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 25%, or a range consisting of any two of these values. When the value of (D1v50-D2v50) / D1v50×100% is in the above range, the adhesion strength of the negative electrode active material particles is high, the particles of the electrochemical device are more stable during cycling, and the expansion rate of the electrochemical device is reduced.

[0047] In some embodiments, the specific surface area of ​​the negative electrode active material particles is 0.8-2.0 m 2 In some embodiments, the specific surface area of ​​the negative electrode active material particles is 0.8 m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m2 / g, 2.0m 2 / g, or a range consisting of any two of these values.

[0048] In some embodiments, the negative electrode active material particles have a specific surface area of ​​B1 before being pressed and a specific surface area of ​​B2 after being pressed at a pressure of 1t, and (B2-B1) / B1×100%≦140%. In some embodiments, (B2-B1) / B1×100% is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, or a range consisting of any two of these values. When (B2-B1) / B1×100% is in the above range, side reactions of the electrochemical device are reduced and the expansion rate is reduced.

[0049] In some embodiments, the negative electrode active material is graphite particles. In some embodiments, the negative electrode active material includes primary graphite particles and secondary graphite particles. In some embodiments, the pores A are stacking gaps between primary graphite particles in the secondary graphite particles. In some embodiments, the pores B are mainly stacking gaps between secondary graphite particles.

[0050] In some embodiments, the secondary graphite particles are prepared from primary graphite particles and a binder, which in some embodiments includes, but is not limited to, low temperature asphalt, medium temperature asphalt, high temperature asphalt, or a resin.

[0051] In some embodiments, when the electrochemical device is discharged to a voltage of 3 V, the specific surface area of ​​the negative electrode active material is 1.9-2.4 m 2 In some embodiments, when the electrochemical device is discharged to a voltage of 3 V, the specific surface area of ​​the negative electrode active material is 1.9 m 2 / g, 2.0m 2 / g, 2.1m 2 / g, 2.2m 2 / g, 2.3m 2 / g, 2.4m 2 / g, or a range consisting of any two of these values.

[0052] In some embodiments, when charged to a voltage of 4.45 V, the maximum exothermic peak of the negative electrode active material layer is 280-330° C. when measured by DSC. In some embodiments, when charged to a voltage of 4.45 V, the maximum exothermic peak of the negative electrode active material layer is 280° C., 286° C., 290° C., 296° C., 300° C., 306° C., 312° C., 318° C., 322° C., 326° C., 328° C., 330° C., or a range consisting of any two of these values ​​when measured by DSC.

[0053] In some embodiments, when the electrochemical device is discharged to a voltage of 3 V, the powder particle size of the negative electrode active material is D a V50, and the powder particle diameter of the negative electrode active material after being pressed at a pressure of 1 ton is D b v50, (D a v50-D b v50) / D a v50×100%≦2%.

[0054] In some embodiments, (D a v50-D b v50) / D a v50×100% is 0.2%, 0.4%, 0.6%, 0.8%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, or a range consisting of any two of these values.

[0055] In some embodiments, when the electrochemical device is discharged to a voltage of 3 V, the negative electrode active material particles have a specific surface area of ​​B 11 And the specific surface area after being pressed with a pressure of 1t is B 22 (B 22 -B 11 ) / B 11 × 100%≦40%. In some embodiments, (B 22 -B11 ) / B 11 × 100% is 4%, 8%, 10%, 12%, 16%, 18%, 20%, 24%, 28%, 32%, 34%, 36%, 38%, 40%, or a range consisting of any two of these values.

[0056] In some embodiments, the electrochemical device includes a lithium ion battery, and the lithium ion battery has an expansion rate of less than 9% after 500 cycles at 25° C. In some embodiments, the lithium ion battery has an expansion rate of less than 8% or less than 7%.

[0057] In some embodiments, the negative electrode active material layer further includes a binder, which may include, but is not limited to, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, or nylon.

[0058] In some embodiments, the negative electrode active material layer includes a conductive material layer, which may include, but is not limited to, natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal powder, metal fiber, copper, nickel, aluminum, silver, or a polyphenylene derivative.

[0059] In some embodiments, the current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, and conductive metal coated polymer substrates.

[0060] In some embodiments, the negative electrode is obtained by a method of preparing an active material composition by mixing an active material, a conductive material, and a binder in a solvent, and applying the active material composition to a current collector.

[0061] In some examples, the solvent may include, but is not limited to, N-methylpyrrolidone.

[0062] 2. Positive electrode The material, structure and manufacturing method of the positive electrode used in the embodiments of the present application include any technique disclosed in the prior art.

[0063] In some embodiments, the positive electrode includes a current collector and a layer of positive electrode active material disposed on the current collector.

[0064] In some embodiments, the positive electrode active material includes, but is not limited to, lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese (NCM) ternary material, lithium iron phosphate (LiFePO4), or lithium manganese oxide (LiMn2O4).

[0065] In some embodiments, the positive electrode active material layer further comprises a binder, and optionally a conductive material layer, which enhances the bonding between the positive electrode active material particles and between the positive electrode active material particles and a current collector.

[0066] In some embodiments, the binder may include, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, or nylon.

[0067] In some embodiments, the conductive material includes, but is not limited to, a carbon-based material, a metal-based material, a conductive polymer, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0068] In some embodiments, the current collector includes, but is not limited to, aluminum.

[0069] The positive electrode can be prepared by a preparation method known in the art. For example, the positive electrode can be obtained by a method of preparing an active material composition by mixing an active material, a conductive material, and a binder in a solvent, and applying the active material composition to a current collector. In some embodiments, the solvent may include, but is not limited to, N-methylpyrrolidone.

[0070] 3. Electrolyte The electrolyte used in the embodiments of the present application may be any electrolyte known in the art.

[0071] In some embodiments, the electrolyte solution includes an organic solvent, a lithium salt, and an additive. The organic solvent included in the electrolyte solution of the present application may be any organic solvent known in the prior art to be used as a solvent for electrolyte solutions. The electrolyte used in the electrolyte solution of the present application is not particularly limited and may be any electrolyte known in the prior art. The additive included in the electrolyte solution of the present application may be any additive known in the prior art to be used as an additive for electrolyte solutions.

[0072] In some embodiments, the organic solvent includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, or ethyl propionate.

[0073] In some embodiments, the lithium salt comprises at least one of an organic lithium salt or an inorganic lithium salt.

[0074] In some embodiments, the lithium salts include, but are not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate LiB(C2O4)2 (LiBOB), and lithium difluorooxalatoborate LiBF2(C2O4) (LiDFOB).

[0075] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.5-3 mol / L, 0.5-2 mol / L, or 8-1.5 mol / L.

[0076] 4. Separator In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the embodiments of the present application are not particularly limited and may be any material disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic material formed from a material that is stable against the electrolyte of the present application.

[0077] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, a film, or a composite film having a porous structure, and the material of the substrate layer is at least one selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite film may be selected and used.

[0078] A surface treatment layer is provided on at least one surface of the base layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer formed by mixing a polymer and an inorganic material.

[0079] The inorganic layer includes inorganic particles and a binder, and the inorganic particles are one or more selected from the group consisting of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium oxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is one or more selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.

[0080] The polymer layer includes a polymer, and the polymer material is at least one selected from the group consisting of polyamide, polyacrylonitrile, acrylic ester polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0081] Electronic Devices The electronic device of the present application is any that uses an electrochemical device in accordance with the embodiments of the present application.

[0082] In some embodiments, the electronic device includes, but is not limited to, a laptop, a pen-based computer, a mobile computer, an e-book player, a mobile phone, a portable facsimile machine, a portable copier, a portable printer, a stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini CD, a walkie-talkie, an electronic notebook, a calculator, a memory card, a portable tape recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, an electric assist bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, a power tool, a flashlight, a camera, a large household storage battery, and a lithium ion capacitor.

[0083] Hereinafter, the preparation of a lithium ion battery will be described with reference to specific examples, taking a lithium ion battery as an example. However, those skilled in the art should understand that the preparation methods described herein are merely exemplary, and any other suitable preparation methods are within the scope of the present application.

[0084] Working Example Hereinafter, the characteristics evaluation of the lithium ion battery according to the present application will be described based on examples and comparative examples.

[0085] 1. Lithium-ion battery manufacturing 1. Manufacturing of negative electrodes 1) Manufacturing of negative electrode active material a) Using petroleum coke as the raw material (i.e., graphite precursor), the petroleum coke and the binder, high-temperature asphalt, were mixed uniformly in a predetermined ratio, and then placed in a horizontal retort, heated to 460°C-550°C, and kept at that temperature for 3 hours to obtain a granulated semi-finished product. b) After that, a graphite negative electrode active material was obtained by a high-temperature graphitization process with a graphitization temperature of 2500°C-3200°C and a graphitization time of 10hr-200hr. The specific process parameters are shown in Table 1.

[0086] 2) Manufacturing of negative electrodes The graphite negative electrode active material, styrene butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) were dispersed in deionized water in a weight ratio of 97.7:1.2:1.1 and thoroughly stirred to uniformly mix to obtain a negative electrode slurry. Acetylene black was applied to a copper foil to obtain a negative electrode current collector. The negative electrode slurry was applied to the negative electrode current collector, dried, and cold rolled to obtain a negative electrode. Graphite particles of different particle sizes were obtained by crushing and classifying the raw material by adopting any known technique.

[0087] 2. Manufacturing of positive electrodes Lithium cobalt oxide (LiCoO2), acetylene black, and polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 96:2:2 with an appropriate amount of N-methylpyrrolidone (NMP) and thoroughly stirred until homogeneous. The mixture was then applied to an aluminum foil as a cathode collector, dried, and cold-rolled to obtain a cathode.

[0088] 3. Preparation of electrolyte In a dry argon gas atmosphere, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a weight ratio of 1:1:1, and LiPF6 was added and mixed uniformly. 3 wt% fluoroethylene carbonate and 2 wt% adiponitrile were added and mixed uniformly to obtain an electrolyte, in which the concentration of LiPF6 was 1.15 mol / L.

[0089] 4. Manufacturing of separators A 12 μm thick polyethylene (PE) porous polymer film serves as the separator.

[0090] 5. Lithium-ion battery manufacturing The positive electrode, separator, and negative electrode were stacked in this order, and the separator was placed between the positive and negative electrodes to provide a separating function, and then the cells were rolled up to obtain a bare cell. After welding the lugs, the bare cell was packed in an aluminum plastic film packaging bag, and the above-prepared electrolyte was injected into the dried bare cell, which was then vacuum sealed, left to stand, formed, shaped, and had its capacity tested to obtain a lithium-ion battery.

[0091] 2.Measurement method 1. Measurement method for pore size distribution of negative electrode active material (mercury intrusion method) The pore size distribution of the negative electrode active material layer was measured using a MicroActive AutoPore V 9600 fully automated mercury intrusion pore size analyzer. The battery was discharged to a voltage of 3 V, disassembled, and the negative electrode was removed and immersed in a dimethyl carbonate solution for 5 hours. The negative electrode (including the negative electrode active material layer and the current collector) was then dried, a dilatometer was attached, and the electrodes were sealed and then placed in the mercury intrusion porosimetry to measure the pore size distribution and pore volume of the negative electrode active material layer. Figure 1 shows differential mercury intrusion curves for Example 11 and Comparative Example 1. The horizontal axis corresponding to the peaks in Figure 1 represents the pore size distribution range, and the area of ​​the peak represents the volume of pores in the material per unit mass. Here, the pore sizes corresponding to the two highest peaks represent the pore sizes of pore A and pore B, and the pore size of pore A is smaller than the pore size of pore B.

[0092] 2. How to measure OI value The OI value of the negative electrode active material layer was measured using an XRD diffractometer. The negative electrode sample was placed in the XRD diffractometer, and the crystal plane areas of the 004 and 110 peaks were measured as C004 and C110, respectively, and the OI value was calculated according to the following formula. The OI value is C004 / C110.

[0093] 3. Method for measuring particle size of negative electrode active material The particle size of the negative electrode active material was measured using a Malvern particle size measuring device. The negative electrode active material sample was dispersed in ethanol, which is a dispersant, and ultrasonically treated for 30 minutes. The sample was then placed in the Malvern particle size measuring device to measure the Dv50, Dn10, and Dv90 of the negative electrode active material.

[0094] 4. Method for measuring the specific surface area of ​​negative electrode active material The specific surface area of ​​the negative electrode active material was measured by the nitrogen adsorption / desorption method using a specific surface area analyzer (Tristar II 3020M). The negative electrode active material sample was dried in a vacuum drying oven, placed in a sample tube, and measured with the analyzer.

[0095] 5, DSC measurement method The lithium ion battery was charged to 4.45 V, then disassembled, the negative electrode was dried, the negative electrode active material layer was scraped off, and the battery was heated to 800°C at a heating rate of 10°C / min in a N2 atmosphere using a synchronous thermal analyzer (STA 449F3). The DSC heat curve was measured.

[0096] 6. How to measure the gram capacity of a lithium-ion battery Discharge the lithium-ion battery to 5.0 mV at 0.05 C, discharge it to 5.0 mV at 50 μA, discharge it to 5.0 mV at 10 μA, and charge it to 2.0 V at 0.1 C, and record the capacity of the lithium-ion battery at this time as gram capacity. 0.05 C refers to a current value that is 0.05 times the design gram capacity, and 0.1 C refers to a current value that is 0.1 times the design gram capacity.

[0097] 7. Measurement method for cycle thickness expansion rate of lithium-ion batteries At 25°C, a micrometer was used to measure the thickness when the lithium-ion battery was below 3.95V as H0. The lithium-ion battery was charged and discharged 500 times at a rate of 1.5C, and the thickness when the lithium-ion battery was at 4.45V was measured every 50 cycles as H0. n The cycle thickness expansion rate of the lithium ion battery was calculated using the following formula: Cycle thickness expansion rate corresponding to the number of cycles = (H n -H0) / H0 × 100%.

[0098] 3. Measurement results Table 1 shows the process parameters for producing the negative electrode active material, in which the amount of binder is the ratio of the weight of binder to the weight of graphite.

[0099] [Table 1]

[0100] The measurement results for related properties are shown in Table 2. Among them, the DSC exothermic peak temperature is used to represent the thermal stability of the negative electrode material, and is the DSC exothermic peak temperature of the negative electrode active material layer when the lithium ion battery is charged to a voltage of 4.45V.

[0101] [Table 2]

[0102] From Examples 1, 5, 9, 13, Examples 2, 6, 10, 14, Examples 3, 7, 11, 15, and Examples 4, 8, 12, 16, when manufacturing the negative electrode active material, if the particle size Dv50 of the petroleum coke, which is the graphite precursor, is not changed, the particle size Dv50 of the graphite particles of the negative electrode active material increases with the increase in the amount of high viscosity binder, the pore size of hole A is almost unchanged, the differential of the amount of mercury penetration increases, and the pore size of hole B and the differential of the amount of mercury penetration increase. This is because the pores of hole A represent the deposition gaps between the primary particles in the secondary particles, and the pores of hole B mainly represent the gaps due to deposition between the secondary particles. If the particle size of the primary particles does not change, the size of the deposition gaps does not change, so the pore size of hole A hardly changes. When the binder content is increased, the more primary particles are compounded in the secondary particles, the more gaps there are, the more the differential of the mercury intrusion amount of pore A increases, and the strength of the compound stability of the secondary particles increases, so that the gaps and number between the particles also increase with the increase in particle size. Therefore, the particle size and differential of the mercury intrusion amount of pore B also increase. After the binder content is increased, the expansion between the particles can be restrained by each other, and the cycle thickness expansion rate of the lithium ion battery is reduced. However, it can be seen from Comparative Example 2 that if the binder content is too high, the gram capacity of the negative electrode active material decreases, affecting its energy density.

[0103] When no high viscosity binder is added in the preparation of the negative active material as in Comparative Example 1, the negative active material is a primary particle and is not composited with secondary particles, so that the particles in the negative active material layer after cold rolling are aligned in the same direction and very tight. The pore size B is small and the differential of mercury penetration is low, so the cycle thickness expansion rate of the lithium ion battery is high and the overall characteristics are poor. When a high content of high viscosity binder is added in the preparation of the negative active material as in Comparative Example 2, the degree of composite between particles is high, the particle arrangement in the negative electrode sheet is isotropic, and the pore size B between particles is large, the differential of mercury penetration is high, and the cycle thickness expansion rate of the lithium ion battery is low. However, the lithium storage performance of the binder is low, which affects the gram capacity of the negative active material. In addition, the particle size of the secondary particles is large, which affects the processability.

[0104] From Examples 1-4, 5-8, 9-12 and 13-16, it can be seen that when the content of high-viscosity binder is constant, with an increase in the Dv50 of the petroleum coke, which is the precursor of the negative electrode active material, the pore size A and its derivative of the amount of mercury intrusion in the negative electrode active material layer increase, the pore size B and its derivative of the amount of mercury intrusion decrease, the OI value increases, and the gram capacity increases, but the thickness expansion rate is affected.

[0105] Table 3 shows the effect of Dv90 and Dn10 of the negative electrode active material on the particle size ratio change value (D1v50-D2v50) / D1v50, the growth rate of the specific surface area (BET), the initial efficiency of the lithium ion battery, and the cycle thickness expansion rate. The negative electrode active material of Examples 17-32 is manufactured from the negative electrode active material of Example 11. By adding screening and classification treatment to the negative electrode active material of Example 11, large particles and fine powder in the negative electrode active material are removed, and the particle size is adjusted.

[0106] D1v50 is the particle size of the powder of the negative electrode active material before it is pressed, D2v50 is the particle size of the powder of the negative electrode active material after it is pressed with a pressure of 1 ton, B1 is the specific surface area of ​​the negative electrode active material before it is pressed, and B2 is the specific surface area of ​​the negative electrode active material after it is pressed with a pressure of 1 ton.

[0107] The method of applying pressure to the negative electrode active material is to use an electronic pressure tester (SUNS UTM7305) to place 1.0±0.05g of the negative electrode active material powder in a die with a diameter of 13mm, apply a pressure of 1t to the negative electrode active material powder, hold it for 5 seconds, and take out the powder after reducing the pressure.

[0108] [Table 3]

[0109] Examples 17-20, 21-24, 25-28, and 29-32 are compared. As a result, when Dn10 is not changed, when Dv90 decreases, the particle size ratio change value (D1v50-D2v50) / D1v50 decreases, the surface area (BET) growth rate decreases, the initial efficiency improves, but the cycle thickness expansion rate increases. Comparing Examples 17, 21, 25, 29, Examples 18, 22, 26, 30, Examples 19, 23, 27, 31, and Examples 20, 24, 28, 32, it can be seen that with an increase in Dn10, the number of fine particles in the negative electrode decreases, the surface area (BET) growth rate increases significantly, the initial efficiency improves significantly, and the expansion improves slightly.

[0110] Throughout the specification, references to "some embodiments," "some embodiments," "one embodiment," "another example," "example," "particular example," or "partial example" mean that at least one embodiment or example of the application includes a particular feature, structure, material, or characteristic described in that embodiment or example. Thus, references throughout the specification, such as "in some embodiments," "in an embodiment," "in one embodiment," "in another example," "in one example," "in a particular example," or "in an example," do not necessarily refer to the same embodiment or example of the application. Furthermore, particular features, structures, materials, or characteristics herein may be combined in any suitable manner in one or more embodiments or examples.

[0111] Although exemplary embodiments have been shown and described, those skilled in the art should understand that the above-described embodiments should not be construed as limiting the present application, and that the embodiments can be modified, substituted, and altered without departing from the technical spirit, principles, and scope of the present application.

Claims

1. a negative electrode comprising: a current collector; and a negative electrode active material layer disposed on the current collector, the negative electrode active material layer comprising negative electrode active material particles, the negative electrode active material particles comprising graphite particles, the negative electrode active material particles comprising secondary particles, the negative electrode active material layer comprising pores A, the pores A having a pore size of 59 nm-73 nm as measured by mercury intrusion porosimetry, and a C004 / C110 value of the negative electrode active material layer being 6-20.

2. When measured by mercury intrusion porosimetry, the differential of the amount of mercury intrusion in hole A was 0.150-0.190 mL / g μm -1 The negative electrode according to claim 1 ,

3. The negative electrode active material layer includes pores B, and when measured by mercury intrusion porosimetry, the pores B have a pore size of 660 nm to 800 nm, and the differential of the amount of mercury intrusion into the pores B is 0.160 to 0.230 mL / g μm -1 The negative electrode according to claim 1 ,

4. 4. The negative electrode of claim 3, wherein the volume ratio of pores B to pores A is 0.7:1-1.42:

1.

5. The negative electrode active material particles are (a) the negative electrode active material particles have a Dv50 of 7.2-21.6 μm; (b) the negative electrode active material particles have a Dv90 of 28.4-40.0 μm; (c) the negative electrode active material particles have a Dv10 of 1.4-9.4 μm; or The negative electrode according to claim 1 , wherein (d) Dv90 and Dn10 of the negative electrode active material particles satisfy at least one of Dv90 / Dn10≦26.

6. The negative electrode active material particles have a powder particle diameter of D before being compressed. 1 v50, and the powder particle size after being pressed at a pressure of 1 tf is D 2 v50, (D 1 v50-D 2 v50) / D 1 2. The negative electrode of claim 1, wherein v50×100%≦25%.

7. The specific surface area of ​​the negative electrode active material particles is 0.8-2.0 m 2 / g.

8. The negative electrode active material particles have a specific surface area of ​​B before being pressed. 1 and the specific surface area after being pressed at a pressure of 1 tf is B 2 (B 2 -B 1 ) / B 1 2. The negative electrode according to claim 1, wherein x 100%≦140%.

9. 9. An electrochemical device comprising the negative electrode according to claim 1.

10. When the electrochemical device is discharged to a voltage of 3 V, the specific surface area of ​​the negative electrode active material is 1.5-2.4 m 2 The electrochemical device according to claim 9 , wherein the molecular weight is 1 / g.

11. 10. The electrochemical device according to claim 9, wherein when the electrochemical device is charged to a voltage of 4.45 V, the maximum exothermic peak of the negative electrode active material layer is 280-330° C. as measured by DSC.

12. When the electrochemical device is discharged to a voltage of 3 V, the powder particle diameter of the negative electrode active material is D a V50, and the powder particle diameter of the negative electrode active material after being pressed at a pressure of 1 tf is D b v50, (D a v50-D b v50) / D a 10. The electrochemical device of claim 9, wherein v50×100%≦2%.

13. When the electrochemical device is discharged to a voltage of 3 V, the negative electrode active material particles have a specific surface area of ​​B 11 and the specific surface area after being pressed at a pressure of 1 tf is B 22 (B 22 -B 11 ) / B 11 10. The electrochemical device according to claim 9, wherein x 100%≦40%.

14. An electronic device comprising an electrochemical device according to any one of claims 9 to 13.

Citation Information

Patent Citations

  • Negative electrode active material, and electrochemical device and electronic device using same

    CN111370695A

  • Negative electrode active material for lithium ion secondary battery, lithium ion secondary battery negative electrode using the same and lithium ion secondary battery

    JP2015187972A

  • Nonaqueous secondary battery

    JP2015220119A

  • Method for manufacturing porous carbon products

    JP2016531818A

  • Sulfide solid battery

    JP2017228455A